Effect of individualized intraoperative lung recruitment maneuver on postoperative pulmonary complications in patients undergoing upper abdominal surgeries under general anesthesia - Mohammad Elhossieny Mohammad Salama; Ezzat Mohamed El-Taher; Ahmad Hamed Abdel-Rahman Al-Touny; Reda Aboelmagd Ismail; Mohamed Emad Eldin Abdel-Ghaffar (Egyptian Journal of Anaesthesia, 2023)
ABSTRACTBackground The concept of lung protective ventilation (LPV) during general anesthesia (GA) aims at minimizing lung injury and postoperative pulmonary complications (POPCs). Recruitment maneuver (RM) as a part of LPV may improve lung mechanics and oxygenation, but despite extensive research, definitive guidelines for the applications of intraoperative RMs have not been established yet.Methods This study was a prospective, single-blinded, randomized clinical trial. Sixty-six subjects undergoing non-laparoscopic upper abdominal surgeries under GA were randomly assigned into two equal groups. Control group (C) received tidal volume of 8 ml/kg predicted body weight (PBW) and positive end expiratory pressure (PEEP) of 5 cmH2O without RM. Recruitment group (R) received tidal volume of 8 ml/kg PBW with stepwise RMs and individualized PEEP titration after each RM. Compliance, plateau pressure, driving pressure, SpO2 and hemodynamics were monitored at each step of RM. POPCs, length of hospital stay and mortality were recorded postoperatively.Results There was a significant reduction in POPCs in (R) group than in (C) group (P = 0.03). Also, there was a significant increase in compliance before extubation in (R) group (P = 0.001). However, no significant difference was noted between both groups as regards mortality rate and length of hospital stay.Conclusion Individualized stepwise lung RM significantly decreases the incidence of POPCs when added to LPV in patients undergoing non-laparoscopic upper abdominal surgeries under GA.